Tales of two cities: political capitals and economic centres in the world city network - Ben Derudder; Peter J. Taylor (Glocalism: Journal of Culture, Politics and Innovation)
The majority of major cities in the world city network are capital cities. Between primacy and political specialization there are examples of countries where the capital city and a second city remain as major rival cities in contemporary globalization. In this paper we focus upon situations where the capital city is less important in global economic capacity: Rome and Milan, Berlin and Frankfurt, Abu Dhabi and Dubai, Delhi and Mumbai, Islamabad and Karachi.